Unlocking the vault: next‐generation museum population genomics. Issue 24 (7th October 2013) - Bi, Ke; Linderoth, Tyler; Vanderpool, Dan; Good, Jeffrey M.; Nielsen, Rasmus; Moritz, Craig
Abstract Natural history museum collections provide unique resources for understanding how species respond to environmental change, including the abrupt, anthropogenic climate change of the past century. Ideally, researchers would conduct genome‐scale screening of museum specimens to explore the evolutionary consequences of environmental changes, but to date such analyses have been severely limited by the numerous challenges of working with the highly degraded DNA typical of historic samples. Here, we circumvent these challenges by using custom, multiplexed, exon capture to enrich and sequence ~11 000 exons (~4 Mb) from early 20th‐century museum skins. We used this approach to test for changes in genomic diversity accompanying a climate‐related range retraction in the alpine chipmunks (Tamias alpinus) in the high Sierra Nevada area of California, USA. We developed robust bioinformatic pipelines that rigorously detect and filter out base misincorporations in DNA derived from skins, most of which likely resulted from postmortem damage. Furthermore, to accommodate genotyping uncertainties associated with low‐medium coverage data, we applied a recently developed probabilistic method to call single‐nucleotide polymorphisms and estimate allele frequencies and the joint site frequency spectrum. Our results show increased genetic subdivision following range retraction, but no change in overall genetic diversity at either nonsynonymous or synonymous sites. This case study showcases the advantages of integrating emerging genomic and statistical tools in museum collection‐based population genomic applications. Such technical advances greatly enhance the value of museum collections, even where a pre‐existing reference is lacking and points to a broad range of potential applications in evolutionary and conservation biology.